2018
DOI: 10.1080/17435390.2018.1489987
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure to silver nanoparticles and cadmium induce metabolic adaptation in HepG2 cells

Abstract: (2018) Co-exposure to silver nanoparticles and cadmium induce metabolic adaptation in HepG2 cells, Nanotoxicology, 12:7, 781-795, DOI: 10.1080/17435390.2018 Although multiple studies have reported the toxicological effects and underlying mechanisms of toxicity of silver nanoparticles (AgNP) in a variety of organisms, the interactions of AgNP with environmental contaminants such as cadmium are poorly understood. We used biochemical assays and mass spectrometry-based proteomics to assess the cellular and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…silver ions, released from the AgNPs present in the periphery (Hadrup and Lam 2014;Mirsattari et al 2004). In vitro studies on various mammalian cells report that AgNPs induce major cytotoxic actions leading to increased cellular apoptosis and cell death (Miethling-Graff et al 2014;Verano-Braga et al 2014;Miranda et al 2018). Other cellular responses, including changes in minor metabolic pathways and protein post-translational modifications, remain largely uninvestigated and may reveal novel actions of nanoparticle toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…silver ions, released from the AgNPs present in the periphery (Hadrup and Lam 2014;Mirsattari et al 2004). In vitro studies on various mammalian cells report that AgNPs induce major cytotoxic actions leading to increased cellular apoptosis and cell death (Miethling-Graff et al 2014;Verano-Braga et al 2014;Miranda et al 2018). Other cellular responses, including changes in minor metabolic pathways and protein post-translational modifications, remain largely uninvestigated and may reveal novel actions of nanoparticle toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have reported that HepG2 cell viability decreased upon exposure to silver NPs. [127][128][129][130] Shanmugasundaram et al found that silver (spherical: 30.5 nm), gold (spherical: 14.5 nm), and silver-gold alloy NPs (spherical: 41.5 nm) conferred protection against DEN-induced HCC in rats through a reduction in tumor volume, blood hepatic biochemical markers and improvement in liver architecture. [131] Other papers have also reported that silver NPs reduce DENinduced HCC symptoms.…”
Section: Metallic Nps and Hepatocellular Cancermentioning
confidence: 99%
“…[143] Silver NPs (spherical: 8-20 nm) and cadmium chloride greatly reduced cell viability in HepG2 hepatocytes, possibly through increased oxidative stress from Nrf2 inactivation. [129] A second heavy metal, lead acetate, was co-administered together with titanium dioxide NPs (50 and 120 nm) to mice, and resulted in increased liver damage. [144] It was found that titanium and lead deposition was increased in liver, kidney and brain tissue after co-treatment, further elevating liver ROS levels and impairing function.…”
Section: Metallic Nps and Toxic Heavy Metalsmentioning
confidence: 99%
“…This resulted in a significant alteration of protein ubiquitination are possibly increased toxicity. The eIF2 signaling pathway was modified after the AgNPs and Cd 2+ exposures, owing to the downregulation of ribosome subunits and proteins involved in translation initiation [141]. Collectively, microenvironmental oxidative stress has settled in several locations.…”
Section: Topology Of Membrane Metabolismmentioning
confidence: 99%